Effect of polydextrose-containing beverage on bowel habits and gastrointestinal symptoms of constipated subjects: a pilot study. - Kurniawan, Mohamad Yulianto; Istiftiani, Nourmatania; Heryati, Lilis; Reinaldo, Christian; Susanto, Fendy (Malaysian Journal of Nutrition, 2020)
Introduction: Indonesians have a low intake of dietary fibre, a key component for an increased incidence in constipation. Available data have documented the benefits of polydextrose (PDX) in healthy subjects. However, data on constipated subjects are lacking. This study aimed to investigate the effect of consuming a PDX (prebiotic) beverage on bowel habits and gastrointestinal symptoms of constipated subjects over seven days. Methods: This was a randomised, non-blinded, nonplacebo- controlled parallel design study involving 24 subjects, divided equally into two groups. Group A (active control group) consisted of 12 subjects, consuming one serving size of 6g PDX beverage. While Group B (intervention group) consisted of 12 subjects, consuming two servings of the same product, containing 12g PDX beverage. Changes in bowel habits (constipation score, stool frequency and stool consistency) and gastrointestinal symptoms (abdominal pain, bloating and flatulence) were monitored. Results: Within seven days, Group B showed 4.9% more reduction in overall constipation mean score than that of Group A. Positive improvement in gastrointestinal symptoms were reported: i.e. abdominal pain (M = -0.08±0.43), bloating (M = -0.29±0.37) and flatulence (M = -0.17±0.47). Majority of subjects had desirable stool frequency (87.5%, >3 defecations/week) and stool consistency (58.3%, type 4). These improvements were due to the fact that PDX provides physiological effects consistent with prebiotic fibre, which alters the gut microbiota composition during the fermentation cycle in the large intestine. Conclusion: Findings of this study suggested that daily PDX beverage consumption effectively improved bowel habits, with fewer constipated subjects reporting of gastrointestinal symptoms.